2005
DOI: 10.1021/ja052794t
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase (GPx)-like Antioxidant Activity of the Organoselenium Drug Ebselen:  Unexpected Complications with Thiol Exchange Reactions

Abstract: The factors that are responsible for the relatively low glutathione peroxidase (GPx)-like antioxidant activity of organoselenium compounds such as ebselen (1, 2-phenyl-1,2-benzisoselenazol-3(2H)-one) in the reduction of hydroperoxides with aromatic thiols such as benzenethiol and 4-methylbenzenethiol as cosubstrates are described. Experimental and theoretical investigations reveal that the relatively poor GPx-like catalytic activity of organoselenium compounds is due to the undesired thiol exchange reactions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
223
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(244 citation statements)
references
References 50 publications
12
223
0
1
Order By: Relevance
“…Selenic acid is unstable and reacts with GSH, forming a selenenyl sulfide adduct (glutathionylated selenenyl). A second molecule of GSH reduces this selenenyl sulfide bond to selenol and generates GSSG (37). These reactions occur in the catalytic center of GSH peroxidases and may require a more hydrophobic environment.…”
Section: Can Selenium Substitute For Sulfur?mentioning
confidence: 99%
“…Selenic acid is unstable and reacts with GSH, forming a selenenyl sulfide adduct (glutathionylated selenenyl). A second molecule of GSH reduces this selenenyl sulfide bond to selenol and generates GSSG (37). These reactions occur in the catalytic center of GSH peroxidases and may require a more hydrophobic environment.…”
Section: Can Selenium Substitute For Sulfur?mentioning
confidence: 99%
“…This is due to the presence of a strong Se···O interaction in compound 6 a, which enhances a thiol exchange reaction at selenium. [18] Therefore, the rate of disproportionation depends on the nature of thiols and strength of the Se···O interactions. When GSH was employed instead of PhSH, the disproportionation selenenyl sulfide that led to the formation of diselenide 6 was significantly faster than that of 6 a.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[13] Although ebselen exhibits interesting therapeutic properties, including anti-inflammatory activity, [7] it is a relatively inefficient catalyst for the in vitro reduction of hydroperoxides with aryl and benzylic thiols (such as PhSH and BnSH) as cosubstrates. [12,15] The relatively poor GPx-like antioxidant activity has been ascribed to undesired thiol exchange reactions that take place at the selenium center in the selenenyl sulfide intermediate. [15] However, ebselen has been shown to be a good antioxidant in vivo, as it exhibits significant GPx activity in the presence of natural thiols such as GSH.…”
Section: Introductionmentioning
confidence: 99%
“…[12,15] The relatively poor GPx-like antioxidant activity has been ascribed to undesired thiol exchange reactions that take place at the selenium center in the selenenyl sulfide intermediate. [15] However, ebselen has been shown to be a good antioxidant in vivo, as it exhibits significant GPx activity in the presence of natural thiols such as GSH. It has been recently shown that ebselen can act either beneficially as a peroxidase mimic, or detrimentally through the depletion of GSH.…”
Section: Introductionmentioning
confidence: 99%